RESEARCH TRENDS ON THE EFFECT OF ENTREPRENEURSHIP EDUCATION ON ENTREPRENEURIAL INNOVATION IN NATIONAL AND INTERNATIONAL JOURNALS: FROM RESEARCH DESIGN TO DATA ANALYSIS - Wahyudi, Eko Juni Wahyudi; Sudarmiatin, Sudarmiatin; Wardana, Ludi Wishnu (International Journal of Business, Law, and Education, 2023)
Entrepreneurship Education is one of the most important platforms to add insight into the world. Entrepreneurship education has many benefits for everyone in developing knowledge that has not been known before to be known. Furthermore, Entrepreneurship Education discusses a lot about an idea related to competence in the business world besides tending to provide the ability to develop creativity and innovation. Furthermore, entrepreneurial innovation creates entrepreneurial success and becomes an opportunity to start a business venture as well as the support services that are already available in the form of career offerings the form of a means to contribute to the economy by creating a job This study uses content analysis on some articles that have been published in national and international journals from 2017 to 2023, with entrepreneurship education and entrepreneurial innovation as the main focus of research. This latest study reveals that in the last three years, the number of publications focusing on entrepreneurship education and entrepreneurial innovation has increased. Among these publications, the most dominant research design is qualitative research. In addition, the research subjects were high school students and university students, respectively, who were targeted in the most articles and material variables. T-test data analysis is the most commonly used instrument and data analysis method in series. In light of the findings of this study, several recommendations have been proposed for future research with entrepreneurship education and entrepreneurial innovation as the main focus. Some of these recommendations include increasing the diversity of research types and selecting more appropriate data analysis techniques